Lack of Effects of Metformin and AICAR Chronic Infusion on the Development of Hypertension in Dahl Salt-Sensitive Rats - Pavlov, Tengis S.; Levchenko, Vladislav; Ilatovskaya, Daria V.; Li, Hui; Palygin, Oleg; Pastor-Soler, Nuria M.; Hallows, Kenneth R.; Staruschenko, Alexander (Frontiers in Physiology, 2017)
In the kidney, reabsorption via the epithelial sodium channel (ENaC) is involved in long-term blood pressure control. Previously we demonstrated that ENaC hyperactivity is associated with development of salt-sensitive (SS) hypertension in Dahl SS rats. AMP-activated kinase (AMPK), playing a role in cellular energy homeostasis, has been shown to decrease ENaC activity. Here we tested whether metformin and AICAR, two drugs that activate AMPK, affect the development of hypertension under high-salt diet. High salt diet significantly increased mean arterial pressure (MAP) in Dahl SS rats. Blood pressure elevation was accompanied by a short-term decline of heart rate and increased circadian arterial pressure dipping. Metformin and AICAR were delivered intravenously at doses of 200 and 20 mg/kg/day, respectively. However, both control and drug-treated groups had similar development of high blood pressure within 3 weeks of 8% NaCl dietary salt intake. In the metformin-treated animals MAP reached 164.9±9.1 mmHg, which was not significantly different from the control group (171.8±5.6 mmHg). Patch clamp analysis revealed that the metformin-treated rats had no difference in the activity of ENaC. AICAR treatment also did not affect the development of hypertension and kidney injury. MAP reached 182.8±4.8 and 178.0±2.8 mmHg in AICAR and vehicle treated groups, respectively. Of note, we found that high-salt diet activated AMPK in the Dahl SS rats, and treatment with these AMPK activators had no significant further effect on AMPK activity. We conclude that AMPK activators, at least under these conditions, do not affect development of hypertension during high-salt diet in the Dahl SS rat model.